Evaluating Healthcare-Associated Infections in Public Hospitals: A Cross-Sectional Study - Daniela Iancu; Iuliu Moldovan; Brîndușa Țilea; Septimiu Voidăzan (MDPI AG, 2023)
Background: Hospital-acquired infections (HAIs) pose a significant danger to global public health, mainly because their numbers are growing exponentially each year. Additionally, the rise of bacterial strains resistant to current treatment options further exacerbates this threat. This study aimed to examine the occurrences of HAIs identified in public hospitals at the county level. Methods: We conducted a cross-sectional study utilizing data provided to the Mures Public Health Directorate from all the public hospitals within the studied county. We examined HAIs reported during the period spanning from 2017 to 2021, which amounted to a total of 4603 cases. Results: The medical departments reported the highest prevalence of HAIs at 48.25%. The most common infections included enterocolitis with Clostridioides difficile (32.61%), COVID-19 (19.83%), bronchopneumonia (16.90%), sepsis, surgical wound infections, and urinary tract infections. The five most frequently identified pathogens were Clostridioides difficile (32.61%), SARS-CoV-2 (19.83%), Acinetobacter baumannii (11.82%), Klebsiella pneumoniae (9.58%), and Pseudomonas aeruginosa (7.95%). Acinetobacter baumannii was the predominant agent causing bronchopneumonia, while Klebsiella pneumoniae was the leading cause of sepsis cases. Escherichia coli was the primary agent behind the urinary tract infections, and Staphylococcus aureus MRSA was identified as the main etiology for wound infections and central catheter infections. Throughout the study period, there was a significant rise in Clostridioides difficile and Gram-negative bacteria prevalence rates. Conclusions: This study identified increased Clostridioides difficile in HAI cases during COVID-19, highlighting the need for careful antibiotic use and emphasizing the growing challenge of multi-resistant strains in post-pandemic state hospitals.